ANALISIS HUBUNGAN UMUR DAN LINGKAR LENGAN ATAS IBU HAMIL DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH DI RSU SRIKANDI IBI JEMBER BULAN JANUARI – MARET TAHUN 2023 - Sri Wulandari, Sulfia Retno; Ermawati, Iit; Lestari, Dwi Anggun (NHM PRESS, 2024)
The incidence of Low Birth Weight Incidence is caused by several factors, including the age of the mother <20/>35 years and the size of the Mid Upper Arm Circumference <23.5 cm. The aim of the study is to analyze the relationship between age and Upper Arm Circumference in pregnant women and the incidence of Low Birth Weight Incidence. The research design was a quantitative analysis with a population of all babies born in January–March 2023 totaling 343. The sampling technique used is simple random sampling (secondary data), so the sample in this study is 182 babies. Data are collected using data collection sheets and analyzed using SPSS version v16 with a chi-square test at a significance level of α<0.005. The results of the study showed that most of the 165 (90.66%) mothers give birth in the age category not at risk, and most of the 173 (95.05%) mothers give birth in the category not at risk of CED, causing Low Birth Weight Incidence 39 (21.43%). Based on statistical tests using chi-square, the results obtained were a p-value of 0.000 (α<0.05) so that there was a correlation between the age of pregnant mother and low birth weight at Srikandi IBI General Hospital in Jember. Based on statistical tests using chi-square, the results obtained were a p-value of 0.003 (α<0.05) so that there was a correlation between the upper arm circumference of pregnant mother and low birth weight at Srikandi IBI General Hospital in Jember. Mothers who are pregnant and give birth at risky ages and with CED tend to give birth to babies with Low Birth Weight Incidence. From the research conducted, it is hoped that health workers will further improve health promotion by carrying out prevention through early detection of pregnancy with ANC examinations.